The Association Between Grip Strength Measured in Childhood, Young- and Mid-adulthood and Prediabetes or Type 2 Diabetes in Mid-adulthood - Fraser, Brooklyn J. (Sports Med, 2020)
BACKGROUND: Although low child and adult grip strength is associated with adverse cardiometabolic health, how grip strength across the life course associates with type 2 diabetes is unknown. This study identified the relative contribution of grip strength measured at specific life stages (childhood, young adulthood, mid-adulthood) with prediabetes or type 2 diabetes in mid-adulthood. METHODS: Between 1985 and 2019, 263 participants had their grip strength measured using an isometric dynamometer in childhood (9–15 years), young adulthood (28–36 years) and mid-adulthood (38–49 years). In mid-adulthood, a fasting blood sample was collected and tested for glucose and glycated haemoglobin (HbA1c). Participants were categorized as having prediabetes or type 2 diabetes if fasting glucose levels were ≥ 5.6 mmol or if HbA1c levels were ≥ 5.7% (≥ 39 mmol/mol). A Bayesian relevant life course exposure model examined the association between lifelong grip strength and prediabetes or type 2 diabetes. RESULTS: Grip strength at each time point was equally associated with prediabetes or type 2 diabetes in mid-adulthood (childhood: 37%, young adulthood: 36%, mid-adulthood: 28%). A one standard deviation increase in cumulative grip strength was associated with 34% reduced odds of prediabetes or type 2 diabetes in mid-adulthood (OR 0.66, 95% credible interval 0.40, 0.98). CONCLUSIONS: Greater grip strength across the life course could protect against the development of prediabetes and type 2 diabetes. Strategies aimed at increasing muscular strength in childhood and maintaining behaviours to improve strength into adulthood could improve future cardiometabolic health. VIDEO ABSTRACT: ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40279-020-01328-2) contains supplementary material, which is available to authorized users.